Identification of the metabolites of ivermectin in humans - Phornpimon Tipthara; Kevin C. Kobylinski; Markus Godejohann; Borimas Hanboonkunupakarn; Alison Roth; John H. Adams; Nicholas J. White; Podjanee Jittamala; Nicholas P. J. Day; Joel Tarning (Wiley, 2021)
Abstract Mass drug administration of ivermectin has been proposed as a possible malaria elimination tool. Ivermectin exhibits a mosquito‐lethal effect well beyond its biological half‐life, suggesting the presence of active slowly eliminated metabolites. Human liver microsomes, primary human hepatocytes, and whole blood from healthy volunteers given oral ivermectin were used to identify ivermectin metabolites by ultra‐high performance liquid chromatography coupled with high‐resolution mass spectrometry. The molecular structures of metabolites were determined by mass spectrometry and verified by nuclear magnetic resonance. Pure cytochrome P450 enzyme isoforms were used to elucidate the metabolic pathways. Thirteen different metabolites (M1‐M13) were identified after incubation of ivermectin with human liver microsomes. Three (M1, M3, and M6) were the major metabolites found in microsomes, hepatocytes, and blood from volunteers after oral ivermectin administration. The chemical structure, defined by LC‐MS/MS and NMR, indicated that M1 is 3"‐O‐demethyl ivermectin, M3 is 4‐hydroxymethyl ivermectin, and M6 is 3"‐O‐demethyl, 4‐hydroxymethyl ivermectin. Metabolic pathway evaluations with characterized cytochrome P450 enzymes showed that M1, M3, and M6 were produced primarily by CYP3A4, and that M1 was also produced to a small extent by CYP3A5. Demethylated (M1) and hydroxylated (M3) ivermectin were the main human in vivo metabolites. Further studies are needed to characterize the pharmacokinetic properties and mosquito‐lethal activity of these metabolites.